Transformation of Banking Law in Indonesia - Gabrielia Febrianty Shofiana; Abd. Shomad; Rahadi Wasi Bintoro (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Globalization development through the market economy system has created injustice for humankind,encouraging Muslims to implement the Sharia in their economic activities. The rapid growth of shariaeconomy in Indonesia, ultimately affects the financial industry, including the banking that implicatesregulation and organizational structure causing two banking systems, namely conventional banking andsharia banking. Based on the description, this paper discusses the national banking law that applies two rulesof law in Indonesia. To address these legal issues, conceptual approach, statutory approach and historicalapproach are used. Based on the analysis, since the enactment of Law Number 21 Year 2008 on Sharia Banking,the existence of sharia banking is getting stronger. Therefore, in Indonesia there is a dual bank system in onerule, namely banking law. Both banks are responsible to bank Indonesia as national central bank.Conventional banks may conduct business activities based on sharia principles, but not so for sharia banks.Keyword: conventional bank, sharia bank, sharia principles